Analisis Strategi Pemasaran Produk Graha Office Di PT. ABC Menggunakan Analisis SWOT dan Marketing Funnel - Rifqi Arfiandi Tri Syahbani; Mega Cattleya PA Islami (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research applies Marketing Funnel and SWOT Analysis to the Graha Office marketing strategy at PT ABC. Funnel stages involve Awereness, Consideration, Purchase, Retention, and Advocacy. The analysis data, including query popularity, market stage, clicks, impressions, and product CTR, are taken from Microsoft Excel. The focus of the research was the internal and external factors affecting the marketing of Graha Office. SWOT analysis identified Strengths, Weaknesses, Opportunities, and Threats. Results show the effectiveness of the Marketing Funnel strategy with full expectations. Achieving customer expectations involves process, product, location, employee attitude, friendliness, convenience, and product arrangement. The SWOT analysis highlights internal components, including management and product strategy, that influence marketing success. The findings form the basis for developing Graha Office's marketing strategy, strengthening its position in the competitive market. The implications of this study serve as a guide in strategic decision-making to deal with market dynamics.